Low-bias control of AMB subject to voltage saturation: state-feedback and observer designs - Tsiotras, P.; Arcak, M. (IEEE transactions on control systems technology, 2005)
This paper addresses the problem of low-bias control for an active magnetic bearing (AMB) subject to voltage saturation. Using a generalized complementarity flux condition, a simple, three-dimensional (3-D) flux-based model is used to describe the dynamics of the low-bias mode of operation. Several stabilizing controllers are derived by applying recent results from nonlinear control theory. Specifically, the asymptotic small-gain theorem of Teel and passivity-based ideas are instrumental in our designs. Both soft and hard saturation constraints are accommodated. When flux measurements are not available, a nonlinear reduced order observer is proposed to estimate the flux. We show global asymptotic stability for all controller-observer interconnections. Numerical simulations against a high-fidelity AMB model show the effectiveness of the proposed control designs.